Outcome of case finding among relatives of patients with known heterozygous familial hypercholesterolaemia. Issue 7275 (16th December 2000) - Bhatnagar, D; Morgan, J; Siddiq, S; Mackness, M I; Miller, J P; Durrington, P N
Abstract: Objectives: To assess the feasibility of detecting new cases of heterozygous familial hypercholesterolaemia by using a nurse led genetic register. Design: Case finding among relatives of patients with familial hypercholesterolaemia. Setting: Two lipid clinics in central and south Manchester. Subjects: 259 (137 men and 122 women) probands and 285 first degree relatives. Results: Of the 200 first degree relatives tested, 121 (60%) had inherited familial hypercholesterolaemia. The newly diagnosed patients were younger than the probands and were generally detected before they had clinically overt atherosclerosis. Concentrations of serum cholesterol were, respectively, 8.4 (1.7 SD) mmol/l and 8.1 (1.9 SD) mmol/l in affected men and women and 5.6 (1.0 SD) mmol/l and 5.6 (1.1 SD) mmol/l in unaffected men and women. Screening for risk factors as recommended in recent guidelines for coronary heart disease prevention would have failed to identify most of the affected relatives in whom hypertension, diabetes mellitus, cigarette smoking, and obesity were uncommon. Conclusions: By performing cholesterol tests on 200 relatives, 121 new patients with familial hypercholesterolaemia were discovered. Because 1 in 500 people in the UK are affected by this condition, to detect a similar number by population screening over 60 000 tests would be required, and only a few of these patients would have been detected had cholesterol testing been restricted to those with other risk factors for coronary heart disease. A case exists for organising a genetic register approach, linking lipid clinics nationally.